Redescription of Arcotheres placunae (Hornell & Southwell, 1909) (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India and Pakistan - Trivedi, Jigneshkumar N.; Vachhrajani, Kauresh D.; Ng, Peter K. L. (Zootaxa, 2018)
The identity of Arcotheres placunae (Hornell & Southwell, 1909) (Pinnotheridae), a pea crab associated with the window pane shell, Placuna placenta, has been confused as the types are lost and the original figures are inaccurate and do not match the description given of the species. In the present study, fresh specimens of the species were collected from the type locality (Gulf of Kachchh, Gujarat, India), and the species is here redescribed and refigured, and its affinities with similar species is discussed. To stabilize the taxonomy of A. placunae, a neotype is chosen from amongst the fresh material.